Control of the infection with Brucella melitensis in cattle: Hussein.A.S , Abd-Alrahman.A.M , Nadia A.A - S., Hussein A. (The Iraqi Journal of Veterinary Medicine, 2008)
Sera from1722 cattle of different age (3 months to 8 years) wereexamined by the Rose Bengal and tube agglutination test: 134 cow givepositive result and the overal Brucella seroprevalence was (8%) milksamples zeropositive milking cattle were cultured on Brucella selecativemedia.Seropositive cattle (102) were treated for the first time with long actingoxytetracyclin at the dose of 20 mg/kg of body weight administeredintramuscularly (i.m) every 2 days for 30 days and streptomycin at 25mg/kg (i.m) every 2 days for 16 days.The regimen was found to be effective in eliminating the shedding ofBrucella organisms by cattle in milk.Moreover all treated cattle became zeronegative within 16 months aftertreatment…zeronegative cattle (1588)were vaccinated for the first timewith the Br.Melitensis as follows1. 362 young cattle(aged three months to one year)were each inoculatedsubcutaneously with a full dose(1×106)viable organisms in 1 ml, Brucellaantibody titers were detected 2-4 weeks post vaccination then decreasedgradually until the animals became zeronegative 8 months aftervaccination.2. 1226cattle aged more than one year were each inoculatedsubcutaneously with reduced dose (1×103 viable organism in 1ml)antibody titers measured 2-4 weeks post vaccination then decreasedgradually until the animals became zeronegative 3 months postvaccination.No Brucella organisms were seen from repeated udeersecretion samples from all vaccinated milking cattle, and no abortionswere recorded among pregnant vaccinated cattle.